2021
DOI: 10.1016/j.jshs.2020.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the COVID-19 pandemic on the physical activity of the Thai population: Evidence from Thailand's Surveillance on Physical Activity 2020

Abstract: Highlights The prevalence of sufficient moderate-to-vigorous physical activity (MVPA) decreased from 74.6% in Thailand's Surveillance on Physical Activity 2019 (pre-pandemic) to 54.7% in SPA 2020 (pandemic period). The decrease in the prevalence of sufficient MVPA was also accompanied by a reduction in the average cumulative minutes of MVPA from 580 to 420. As was the case in the pre-pandemic period, Thai males accumulated a higher level of physical activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
98
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(118 citation statements)
references
References 27 publications
4
98
1
2
Order By: Relevance
“…This is exactly the share of the population as reported in British surveys for the UK [ 29 ]. During a pandemic, where population levels of sport and exercise generally declined in many countries [ 22 , 35 , 36 , 37 , 38 ], digital sports became more popular.…”
Section: Discussionmentioning
confidence: 99%
“…This is exactly the share of the population as reported in British surveys for the UK [ 29 ]. During a pandemic, where population levels of sport and exercise generally declined in many countries [ 22 , 35 , 36 , 37 , 38 ], digital sports became more popular.…”
Section: Discussionmentioning
confidence: 99%
“…These studies support our finding that, although restrictions confined people to their home, they found alternative ways to keep their habitual physical activity level. Conversely, based on online physical activity questionnaires, a study from Thailand did not show any increase in physical activity after the lockdown was lifted [ 23 ], and a study from Bangladesh showed a high prevalence of inactivity during lockdown [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been done regarding other aspects of health, such as the adoption of preventive behaviours in older people 14 and the level of physical activity among both young and older adults. 15 The protection of public health and safety is of primary importance especially during public health emergencies, but psychological health and well-being also need attention. One study examined anxiety experienced due to COVID-19, but it concerned only the general population of Bangkok.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%